Logit And Complementary Log-Log Modeling (Case Study: Factors Influencing Birth Control Use in Papua 2017) - Riza Sasmita; Yenni Kurniawati; Sri Wahyuni; Celsy Aprotama (UNP Journal of Statistics and Data Science, 2025)
Research was conducted to determine the factors that influence the use of family planning in Papua Province in 2017. Indonesia has the 4th largest total population in the world, facing the challenge of a fairly high and uncontrolled population growth rate, which can have an impact on the welfare of the community, especially Papua Province. This study used secondary data from the 2017 SDKI. The population of this study was all women of childbearing age in the province of Papua. The research was conducted using logit logistic regression and cloglog logistic regression methods and took the best model to analyze the factors affecting family planning use in Papua Province. The results showed that the cloglog logistic regression model proved to be the best model based on AIC and accuracy. The accuracy of this cloglog logistic regression model is 78.54%. With the results of the cloglog logistic regression analysis, it was found that there was a relationship between region of residence, husband's education, and wife's education. The odds of a woman who has a husband with more than a junior high school education having an unmet need for family planning is 1.688 times higher than a woman who has a husband with less than a junior high school education. The odds of a woman with a junior high school education or above having an unmet need for family planning is 0.496 times higher than a woman with less than a junior high school education.